The Effect of Pedagogic Competence, Academic Supervision, and the Work Environment on Performance Through Work Motivation - Farida, Farida; Rusdarti, Rusdarti; Yusuf, Amin (Educational Management, 2021)
This study aims to analyze the effect of pedagogic competence, academic supervision, work environment on teacher performance through work motivation as an intervening variable in SMK Negeri Kabupaten Batang. Teacher performance is the result of work or work performance carried out by a teacher based on his ability to manage teaching and learning activities in the classroom. The population in this study were all State Vocational School teachers in Batang Regency as many as 277 people. The sample size of the study sample was 160 teachers. Sampling was done by proportional random sampling. The research instrument used was a questionnaire which first tested its validity and reliability. Data analysis for hypothesis testing used path analysis and Sobel test to test the mediating variables. The results showed: (1) Pedagogic competence, academic supervision, work environment, have a direct effect on work motivation, the effect is positive and significant. (2) Pedagogic competence, academic supervision, and work environment have a direct and indirect effect on teacher performance by mediating work motivation, the effect is positive and significant. Professional guidance provided by principals to teachers is an effort that provides opportunities for teachers to develop professionally so that they are even better in carrying out their main task of teaching in the classroom. These teachers become able and willing to improve and enhance the learning abilities of students.